Electroanalytical Performance of Graphene Paste Electrode Modified Al(III)-TiO2 Nanocomposites in Fipronil Solution - Nurdin, Muhammad; Arham, Zul; Rahayu, Sri; Agus Salim, La Ode; Maulidiyah, Maulidiyah (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
The new composite material Al(III)-TiO2 has been synthesized and applied as a modifier of graphene paste electrode for the determination of fipronil pesticide by cyclic voltammetry. The methods were to synthesis of Aluminum-Titanium dioxide (AT), preparation of graphene paste electrode with mass varied Al(III)-TiO2 (GAT) (0.05 g, 0.1 g, 0.2 g), and fipronil electroanalytic respons. Addition of Al(III)-TiO2 to the graphene paste electrode shows redox properties which are well characterized by a fast electron transfer process. Based on the results of measurements in a solution containing fipronil, it is known that fipronil is oxidized at a potential value of 0.26 V. Furthermore, the fipronil oxidation process on the GAT surface is influenced by diffusion control, this is powered by R2 value 0.91 when plotted between peak oxidation currents (Ipa) vs. root scan rate. Other results show that measurement linearity is in the range 0.01 to 0.09 g/L with a limit of detection (LOD) value of 0.0164 g/L. Moreover, GAT shows good stability in the determination of fipronil with% RSD equal to 5%.